INVESTIGATION OF THE ACTIVITY LEVEL AND RADIOLOGICAL IMPACTS OF NATURALLY OCCURRING RADIONUCLIDES IN BLAST FURNACE SLAG - Turhan, Şeref; Uğur, F.A.; Şahan, H.; Gören, E.; Gezer, F.; Yeğingil, Z. (Radiation Protection Dosimetry (2012), pp. 1–7, 2012)
The activity level and possible radiological impacts of naturally occurring radionuclides on the health of workers and members of the public, as a result of utilisation of blast furnace slag (BFS) samples as a substitute for aggregate in road construction were investigated by using a gamma-ray spectrometer and potential exposure scenarios given in Radiation Protection 122. The mean activity concentrations of the 226Ra, 232Th and 40K in BFS samples were found to be 152.4, 54.9 and 183.1 Bq kg21, respectively. These values are compared with typical values measured in BFS samples from the European Union countries, which are 270, 70 and 240 Bq kg21 for 226Ra, 232Th and 40K, respectively. The values of radium equivalent activity index calculated for BFS samples were within the recommended safety limits. The highest total annual effective doses evaluated as 0.9 and 0.4 mSv y21 for members of the public and workers, respectively, were lower than the annual limit of 1 mSv y21.
Keywords: ACTIVITY LEVEL,RADIOLOGICAL IMPACTS